Gaya Bahasa Persuasif Afiliator Pada Aplikasi Tiktok - Reza, Muh. Arfah; Saleh, Muh.; Usman, Usman (Fakultas Teknik Universitas Negeri Makassar, 2024)
This study aims to describe the techniques of affiliator persuasive language in the Tiktok application and describe the function of affiliator persuasive language in the Tiktok application. This research uses a descriptive qualitative approach, data sources from the Tiktok application. The form of data in this study are sentences, phrases, and quotations in affiliator videos on the Tiktok application. The data collection techniques in this research are note-taking, reading, and documentation techniques. The data analysis techniques in this research are data reduction, data presentation, and data verification. The results showed that there are techniques of affiliator persuasive language in the Tiktok application that can be known, namely rationalisation, identification, suggestion, conformity, substitution and compensation. The functions of the affiliator's persuasive language on the Tiktok application found, namely to influence decisions and to change views.